Development And Impact Of Financial Technology (Fintech) On The Islamic Financial Industry Perumda BPR Majalengka - Lutfi Rohmawati; Poy Saefullah Zevender; Lathifahturahmah Lathifahturahmah; Tasiman Tasiman; Widayati Widayati (PT. Publikasiku Academic Solution, 2022)
The purpose of this study was to examine how the development and impact of Fintech on the Islamic finance industry in Majalengka. The research method used is descriptive qualitative method and combines two types of research, namely field research and library research. Field research by collecting information from the Financial Services Authority (OJK) Majalengka, and from the Islamic Finance industry, namely Perumda BPR Majalengka. Along with the development of technology, the financial industry is also growing with the emergence of Fintech (financial technology). Fintech is one of the innovations in the financial sector that refers to modern technology. The development of Fintech so that Sharia-based Fintech appears and facilitates customers will certainly affect the formal Islamic finance industry such as Islamic Banks, Sharia BPRS, BMTs and other formal Islamic finance industries where transactions in the formal Islamic finance industry still use physical transactions. in transactions and have not made much use of technological advances that are growing. This will make the formal financial industry less effective because it costs more and takes more time. If the Islamic finance industry is not able to innovate and utilize technology, it will be left far behind by the Fintech-based financial industry which is developing very rapidly.